1993
DOI: 10.1007/bf00761030
|View full text |Cite
|
Sign up to set email alerts
|

Community support services and functioning of the seriously mentally ill

Abstract: A cohort of 729 chronically mentally ill patients receiving community support services (CSS) were followed over a nine-month period. Receiving needed community support services was shown to predict change in client functioning as measured by the Global Assessment Scale (GAS) even after the initial values on the GAS, as well as demographic, psychiatric, residential and medication maintenance variables were considered. Adequacy of social support from family, friends and others also contributed to predicting chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Inmates of jails (at least large, urban jails) have rates of schizophrenia, major depression, and bi-polar disorder 2±3 times higher than the general population (Teplin, 1990). In Ohio, site of the present study, a 1987 study of mental disorder among state prison inmates found that 12% had serious psychiatric disorders, while 22% had psychiatric disorders at some time in their lives (Bean, Meirson, Pinta, & Melvin, 1988). In Ohio, site of the present study, a 1987 study of mental disorder among state prison inmates found that 12% had serious psychiatric disorders, while 22% had psychiatric disorders at some time in their lives (Bean, Meirson, Pinta, & Melvin, 1988).…”
Section: The Research Populationmentioning
confidence: 54%
See 1 more Smart Citation
“…Inmates of jails (at least large, urban jails) have rates of schizophrenia, major depression, and bi-polar disorder 2±3 times higher than the general population (Teplin, 1990). In Ohio, site of the present study, a 1987 study of mental disorder among state prison inmates found that 12% had serious psychiatric disorders, while 22% had psychiatric disorders at some time in their lives (Bean, Meirson, Pinta, & Melvin, 1988). In Ohio, site of the present study, a 1987 study of mental disorder among state prison inmates found that 12% had serious psychiatric disorders, while 22% had psychiatric disorders at some time in their lives (Bean, Meirson, Pinta, & Melvin, 1988).…”
Section: The Research Populationmentioning
confidence: 54%
“…They found that consumers who reported unmet needs also reported more symptoms and lower quality of life. Similarly, Baker andcolleagues' (1992, 1993) survey of case managers found that community support services enhanced global functioning. Similarly, Baker andcolleagues' (1992, 1993) survey of case managers found that community support services enhanced global functioning.…”
Section: Literature Review Social Support For Chronically Mentally Ilmentioning
confidence: 99%
“…A total of 13 questions were used to measure peer behavior, all of which were drawn from work previously conducted by Stiffman, Dore, Cunningham, and Earls (1995) and Baker, Jodrey, Intagliata, and Straus (1993). The 13 questions were used to create three subscales: positive peer behavior (r = .58), negative peer behavior (r = .83), and peer substance use (r = .83).…”
Section: Community Level Protective Factorsmentioning
confidence: 99%
“…Models of services to this population have tended to be urban in design, however, and not specifically suited for the needs and resources of rural settings (Bachrach 1982). Baker and Intagliata (1984) reviewed case management and other community support services provided to persons with severe mental illness in rural and urban settings. They found that the range of community support services offered to rural and urban residents was about the same.…”
Section: Services To Special Populations: An Overview Of Clinical Issuesmentioning
confidence: 99%